Health aspects of wireless communication schwannomas of the acoustic nerve and the use of mobile phones. - Lin, James C.
In a recently reported study, an increased risk of acoustic neuroma (also known as schwannoma) was found among persons in Sweden with 10 or more years of mobile-phone use [1]. There was no association with use less than 10 years, nor for other measures of use such as total hours of use or total number of calls made.
Keywords: Computer Systems Organization; Computer communication networks; Network architecture and design; Wireless communication; Computer applications; Life and medical sciences; Health; Human factors